Landscape-scale forest cover drives the predictability of forest regeneration across the Neotropics. Issue 1990 (11th January 2023) - Arroyo-Rodríguez, Víctor; Rito, Kátia F.; Farfán, Michelle; Navía, Iván C.; Mora, Francisco; Arreola-Villa, Felipe; Balvanera, Patricia; Bongers, Frans; Castellanos-Castro, Carolina; Catharino, Eduardo L. M.; Chazdon, Robin L.; Dupuy-Rada, Juan M.; et al.
Abstract : Abandonment of agricultural lands promotes the global expansion of secondary forests, which are critical for preserving biodiversity and ecosystem functions and services. Such roles largely depend, however, on two essential successional attributes, trajectory and recovery rate, which are expected to depend on landscape-scale forest cover in nonlinear ways. Using a multi-scale approach and a large vegetation dataset (843 plots, 3511 tree species) from 22 secondary forest chronosequences distributed across the Neotropics, we show that successional trajectories of woody plant species richness, stem density and basal area are less predictable in landscapes (4 km radius) with intermediate (40–60%) forest cover than in landscapes with high (greater than 60%) forest cover. This supports theory suggesting that high spatial and environmental heterogeneity in intermediately deforested landscapes can increase the variation of key ecological factors for forest recovery (e.g. seed dispersal and seedling recruitment), increasing the uncertainty of successional trajectories. Regarding the recovery rate, only species richness is positively related to forest cover in relatively small (1 km radius) landscapes. These findings highlight the importance of using a spatially explicit landscape approach in restoration initiatives and suggest that these initiatives can be more effective in more forested landscapes, especially if implemented across spatial extents of 1–4 km radius.